Analisis Prioritas Pengembangan Kawasan Objek Wisata Alam di Desa Tiwingan Lama - Lurianto Setiawan; Saipudin Saipudin (PPJP Universitas Lambung Mangkurat, 2022)
This study aims to (1) find out how the contribution of each criterion to the development of natural tourism objects in Tiwingan Lama Village, Aranio District, Banjar Regency, and (2) find out what alternative options are priority to be developed in Tiwingan Lama Village, Aranio District, Banjar Regency.Respondents in this study were 7 respondents who were considered experts and influenced the determination of the development of the tourism village area in Tiwingan Lama Village, which were used in data processing using the AHP (methodAnalytical Hierarchy Process).The results of this study indicate that the criteria for regional policies, regional potential, number of visitors, and community income influence the prioritization of the development of tourism village areas in the order of 27.7% regional policy preference values, 46.6% regional potential, 16.1% number of visitors, and 9.6% of people's income. Based on the three alternatives of priority selection for the development of the tourist village area, the alternative or potential for the Matang Kaladan hill has the highest preference value of 59.6%, Alimpung Park hill 23.8%, and Atawang hill 16.6%. With the most dominant conclusion is the Matang Kaladan hill (59.6%).